PENGARUH PENDIDIKAN KEWIRAUSAHAAN, SIKAP MANDIRI DAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI TULUNGAGUNG - Farhaturrahmah, Melany; Sunaryo, Agus; Umami, Nailariza (Relawan Jurnal Indonesia, 2025)
This study aims to determine how entrepreneurial interest at Bhinneka PGRI University Tulungagung is influenced by entrepreneurship education, independent attitude and social media in students of the Economic Education Study Program. This study uses a Questionnaire and is Quantitative. A total of 117 students of semester 6 and semester 8 of Economic Education at Bhinneka PGRI University participated in this study. The sampling technique used is Probability Sampling Technique specifically Proportionate Stratified Random Sampling. This study uses SPSS 25 software. The results of the equation Y = 5.786 + 0.323X1 + 0.480X2 + 0.114X3 in multiple linear regression. These three factors significantly influence students' entrepreneurial interest. Partially, variable (X1) entrepreneurship education tcount 5.230 > ttable 1.98118, variable (X2) independent attitude tcount 7.593 > ttable 1.98118 and variable (X3) social media tcount 1.991 > ttable 1.98118. Simultaneously, the three variables have a significant effect with Fcount 90.649 > Ftable 3.08. The three variables contribute 69.9% of the variation in entrepreneurial interest with an Adjusted R Square of 0.699, while 30.1% is influenced by other factors. Students need to prioritize the development of an independent attitude (X2) because it has a greater influence on student interest with a regression coefficient of 0.480 compared to entrepreneurship education (X1) which has a regression coefficient of 0.323 and social media (X3) which has a regression coefficient of 0.114.